Barthes / Fontana Modern Masters - Culler Jonathan; Kermode Frank (Fontana Press, 1990)
Man of Parts, Literary Historian, Mythologist, Critic, Polemicist, Semiologist, Structuralist, Hedonist, Writer, Man of Letters, Bibliography.
Man of Parts, Literary Historian, Mythologist, Critic, Polemicist, Semiologist, Structuralist, Hedonist, Writer, Man of Letters, Bibliography.